From goals to engagement—evaluating citizen science project descriptions as science communication texts - Golumbic, Yaela N.; Oesterheld, Marius (Frontiers in Environmental Science, 2023)
Attracting and recruiting volunteers is a key aspect of managing a citizen science initiative. Science communication plays a central role in this process. In this context, project descriptions are of particular importance, as they are very often, the first point of contact between a project and prospective participants. As such, they need to be reader-friendly, accessible, spark interest, contain practical information, and motivate readers to join the project. This study examines citizen science project descriptions as science communication texts. We conducted a thorough review and analysis of a random sample of 120 English-language project descriptions to investigate the quality and comprehensiveness of citizen science project descriptions and the extent to which they contain information relevant to prospect participants. Our findings reveal information deficiencies and challenges relating to clarity and accessibility. While goals and expected outcomes were frequently addressed, practical matters and aspects related to volunteer and community management were much less well-represented. This study contributes to a deeper understanding of citizen science communication methods and provides valuable insights and recommendations for enhancing the effectiveness and impact of citizen science.